Islamic Economic Development Through Halal Businesses Among Malaysian Community - Hasan, Ahmad; Maimunah, Sukeri (2015)
Since its dependence in 1957, Malaysia has rapidly grown in economy. Malaysia has also been recognized as most developing Islamic country and aspired to be the world halal hub in 2020. Halal industry or more recently referred to halal economy is one of the fastest growing business segments in the world today. Halal economy comprised of halal food, modest fashion, Muslim-friendly travel, media and recreation, pharmaceuticals and cosmetics as well as Islamic finance. Among these, halal food and Islamic finance is one of the biggest contributors in halal development industry especially in Malaysia. The number of Muslim worldwide are increasing, however, the availability of halal products are still inadequate to supply the demands for the Muslim population which means that the Muslim markets are still under-served. The value of global halal economy is estimated at RM 8.4 trillion and almost RM 2.5 trillion of that total comes from halal food sector. Malaysian Government has taken many initiatives to develop the halal economy in Malaysia. One of this is by incorporation of HDC to help SMEs and works with all the relevant ministries and agencies among the halal industry players. HDC also facilitates and support Halal entrepreneurs to penetrate the Halal global market through branding, marketing and promotional campaigns of halal products. With this kind of effort from the government, Malaysian community especially SMEs should grab the chance by joining this lucrative halal market and ventured internationally as well as contribute to the developing of Islamic economic domestically and globally.